Resting right ventricular systolic function parameters are not associated with peak exercise cardiorespiratory function in healthy adolescent elite male athletes - Williams, C. A.; Dorobantu, D. M.; Wadey, C.; Ryding, D.; McNally, S.; Perry, D.; Stuart, A. G.; Pieles, G. E. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The relationship between right ventricular (RV) systolic function and cardiorespiratory fitness is complex, especially during exercise, when cardiac output and oxygen uptake (VO2) change in relation to one another. Previous small studies have alluded to a possible correlation between resting RV function and peak VO2 in young athletes. The aim of this study was to investigate this relationship using a large cohort of healthy elite adolescent football players.